Turbulente Energie- und Impulsflüsse in der atmosphärischen Grenzschicht über dem polaren Ozean - Lüpkes, Christof; Schmitt, Amelie; Gryanik, Vladimir (Deutscher Wetterdienst, 2018)
This contribution explains relevant processes in the polar atmospheric boundary layer. The focus is on the turbulent exchange, which is most important for the interaction between atmosphere, sea ice and ocean. This interaction depends on different governing factors such as the flow regimes, the sea ice cover, wind direction relative to the orientation of the pack ice edge and the distance of a location to the pack ice edge. The interaction processes are especially complex over fractional sea ice cover. Over such regions the exchange is not only influenced by strong contrasts between surface and air temperatures but also by form drag casued by floe edges. This is demonstrated by explaining a parameterization of transfer coefficients for momentum and energy which is well suited for the application in climate and weather prediction models.